The Capacity of Republika Srpska for Developing of Small and Middle Enterprises - Лазо Рољић, PhD (Acta Economica, 2006)
The experiences in developed countries shown that small and midlle enterprises has become the generator of development of whole economy and employing of people. The small enterprises are much more reliable on market demand, and they are able to rich a better financial results but by angaging of less business assets (fixed assets and working capital). They also contribute to permanent increase of employment. Just from that reason, the role of SME in total economy development of Republika Srpska in some last years has become more apparent. Small economy is dominant part of total economy measured by number of business subjects, by financial results, and also by number of employed people, compared by whole economy of Republika Srpska.